Efek Mediasi Komitmen Organisasi pada Pengaruh Motivasi Terhadap Kinerja Pegawai pada Rumah Sakit Umum Negara: Penelitian - Intan Candradewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the mediating effect of organizational commitment on the influence of motivation on employee performance at the Negara General Hospital. The population in this study was all 72 doctors working at the Negara General Hospital. Data collection methods used were observation, interviews, and questionnaires. The sampling technique used was a census or saturated sampling technique. Path analysis was used for data analysis. The analysis found that 1) motivation has a positive effect on organizational commitment among Negara General Hospital employees; 2) motivation and organizational commitment have a positive effect on employee performance at the Negara General Hospital; 3) motivation has a positive effect on employee performance at the Negara General Hospital through organizational commitment. This study recommends that Negara General Hospital management can improve motivation and organizational commitment to improve employee performance at the Negara General Hospital.